Evaluating the Impact of Conservation Agriculture on Soil Structure and Glyphosate Degradation - Harris, Matthew (2024)
Conservation agriculture (CA) is a set of practices used by farmers with the aim of building soil health and reducing inputs. A key tenant of CA is the reduction of tillage; however, this can leave CA practitioners vulnerable to heavy weed burdens. As such, many rely on glyphosate, the most used herbicide on the planet, to control weeds. While considered to pose a low risk to human, animal and environmental health, concerns about glyphosates long term, chronic impacts are mounting and interest into the factors affecting the molecules persistence is growing. This research uses X-ray Computed Tomography (XRCT) of intact soil cores coupled with liquid chromatography tandem mass spectrometry (LC-MS/MS) along a post-application time series, as well as a complimentary laboratory-based incubation experiment to investigate how the soil structure of a cultivated and uncultivated field affects glyphosate degradation. XRCT data showed total porosity increased two fold after cultivation, and quantifiable levels of glyphosate dropping to zero after cultivation while appreciable levels continued to be detected in the uncultivated soil for several weeks longer. Also discussed are two other experiments, one comparing the effects of strip-tillage (ST) on soil structure; the other a pilot for a protocol to evaluate the effects of arbuscular mycorrhizal fungi (AMF) on soil structural genesis and evolution.